'Are You Local?' Indigenous Iron Age and Mobile Roman and Post-Roman Populations: Then, Now and In-Between. (8th November 2018) - Hingley, Richard; Bonacchi, Chiara; Sharpe, Kate
Abstract: The Iron Age and Roman periods are often defined against each other through the establishment of dualities, such as barbarity–civilisation, or spiritual–rational. Despite criticisms, dualities remain prevalent in the National Curriculum for schools, television, museum displays and academic research. Recent scientific studies on human origins, for example, have communicated the idea of an 'indigenous' Iron Age, setting this against a mobile and diverse Roman-period population. There is also evidence for citizens leveraging dualities to uphold different positions on contemporary issues of mobility, in the UK and internationally. This paper discusses values and limitations of such binary thinking, and considers how ideas of ambiguity and temporal distancing can serve to challenge attempts to use such dualities to map the past too directly onto the present, reflecting on recent social media debates about Britain and the European Union.